The succession of a contaminated floodplain: reclaiming the West Bottoms - King, Jessica (Kansas State University, 2013)
Kansas City is expecting a 25% growth in population by 2050. This design proposal promotes West Bottoms as a potential area to house some of the new population, and more importantly supply a live and work community for these people. West Bottoms is also home to major industry in Kansas City as well as an up and coming art culture. West Bottoms has great potential for a community that allows the existing and new population to be a part of a live-work-play community with the vacancies in the area. The projected population growth is expected to promote sprawl, further increasing the average driving time to the city. West Bottoms currently has few connections to the downtown and offers few reasons to come to the area. These connections are mainly major bridges or highways. Another issue West Bottoms faces is flooding problems from OK Creek and Turkey Creek, which lead into the Kansas and Missouri Rivers. Finally, post and present industrial soil contamination threatens the groundwater. When mixed with flooding concerns, this contamination is potentially harmful for the health of downstream cities. Drawing inspiration from travels, Kansas City charm, plants, art, and water storage, case studies were researched. Themes from each case study were quantified. These themes paired with inventory and analysis of the West Bottoms provided the basis for the design proposed here. The successional design of the area will progress from a contaminated landscape to a landscape that holds floodwater. The final design holds all of the stormwater from the 100 year 1, 2, 3, 6, 12, and 24 hour rain events. The final design incorporates areas of learning, a variety of paths and seating, a live-work-play community, clean and creative industry, and an art culture that sustains the excitement for the timeline of succession. Overtime this landscape will evolve into a new destination for Kansas City using an integrated solution remediating the soil and holding flood waters as an amenity for the new population.
Keywords: Natural Succession; Flood Storage; Phytoremediation; West Bottoms, Kansas City; Wastewater Treatment; Informal Environmental Learning; Area Planning and Development (0341); Design (0389); Ecology (0329); Environmental education (0442); Environmental Health (0470); Environmental Studies (0477); Landscape Architecture (0390); Land Use Planning (0536); Plant Sciences (0479); Sustainability (0640); Urban Planning (0999); Water Resource Management (0595)